2011
DOI: 10.3390/w3010217
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Midwestern Residents Perceptions of Water Quality

Abstract: Abstract:The plurality of conservation and environmental viewpoints often challenge community leaders and government agency staff as they seek to engage citizens and build partnerships around watershed planning and management to solve complex water quality issues. The U.S. Midwest Heartland region (covering the states of Missouri, Kansa, Iowa, and Nebraska) is dominated by row crop production and animal agriculture, where an understanding of perceptions held by residents of different locations (urban, rural no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…To design an effective participatory watershed management process, government agencies need to account for the degree of the heterogeneity in opinions about water quality and pollution sources of the target community. This study shows that similar to the results reported for other regions (Hu and Morton, 2011), in the southern United States, the degree of the heterogeneity of citizens’ opinions about the impacts of nutrients and pathogens on local water quality, as well as about the relative contributions of the potential pollution sources, depends on residency in urban or rural areas and involvement in agriculture, as well as on demographic characteristics. We found that younger, female, urban dwellers are generally more concerned about fertilizer and pathogen water quality issues than are older, male, rural dwellers (and those particularly involved in agriculture).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…To design an effective participatory watershed management process, government agencies need to account for the degree of the heterogeneity in opinions about water quality and pollution sources of the target community. This study shows that similar to the results reported for other regions (Hu and Morton, 2011), in the southern United States, the degree of the heterogeneity of citizens’ opinions about the impacts of nutrients and pathogens on local water quality, as well as about the relative contributions of the potential pollution sources, depends on residency in urban or rural areas and involvement in agriculture, as well as on demographic characteristics. We found that younger, female, urban dwellers are generally more concerned about fertilizer and pathogen water quality issues than are older, male, rural dwellers (and those particularly involved in agriculture).…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have shown that urban residents may share more concerns about environmental issues than do rural residents, although the difference depends on the measure of environmental concern used by the researchers (e.g., Arcury and Christianson, 1990; Morrissey and Manning, 2000). Those residing in rural areas generally perceive their water to be of better quality and less affected by such sources of pollution as farming and timber harvesting (Hu and Morton, 2011). This difference in perceptions can be explained by the more pronounced exposure to environmental degradation in urban areas.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on farmers' perception of water quality and pollution reduction measures and adoption of associated BMPs have been conducted over the last few decades with most of them being conducted in the US (Lichtenberg and Lessley, 1992;Ryan et al, 2003;Morton, 2007;Popp et al, 2007;Kaplowitz and Witter, 2008;Hu and Morton, 2011;Savage and Ribaudo, 2013). Bratt (2002), analyzes Swedish farmers' choices for management practices aimed at reducing nutrient pollution at the catchment level, while Sang (2008) studies farmers' preference for catchment management practices in Scotland.…”
Section: Previous Studies and Conceptual Modelmentioning
confidence: 99%